Public-Private-Civil Society Partnership: A Gateway to Ensuring Good Governance Practices of Vocational Education Programme in South-South Nigerian Federal Universities - Edokpolor, James Edomwonyi; Edokpolor, James Edomwonyi (Journal of Technical Education and Training, 2019)
There is an increasing evidence that education generally and vocational education particularly in Nigeria is facing serious challenge of financial resource mismanagement, which seem to be traceable to high level of corruption or corrupt practices exhibited by school administrators. This unpleasant situation has contributed to lack of effectiveness and efficiency, accountability, transparency, and integrity in the utilization of funds for execution of projects. However, the quest to achieve the main objectives of vocational education appears to be rather unrealistic. Therefore, the issue of mismanagement or lack of clarity in the utilization of funds for execution of projects have called for the coalition of all major stakeholders within and outside Nigeria so as to help bypass the corrupt governance of vocational education programme. This study aims at investigating the extent to which public-private-civil society partnership (PPCSP) can help in establishing good governance practices of vocational education programme in Federal Universities in South-South geopolitical region of Nigeria. Four research questions were raised and answered using the Mean and standard deviations descriptive statistics, and four corresponding null hypotheses were formulated and tested using the t-test statistic. A descriptive survey research design was employed for the study. The study population comprised of all the vocational education lecturers in South-South Nigerian Federal Universities. A 4-point scaled questionnaire was administered to 154 vocational education lecturers. The instrument was validated by 4 experts, and the reliability coefficient using Cronbach alpha was Î±=.90. The analysis of the data collected revealed that to a very high extent PPCSP can help in promoting good governance practices (e.g., effectiveness, efficiency, transparency, accountability, and integrity) in the utilization of funds for execution of projects by vocational education administrators. When the corresponding null hypotheses were tested, the study found no significant difference in the Mean responses of male and female vocational education lecturers as regards the extent to which PPCSP can help in promoting good governance practices in the utilization of funds for execution of projects. Based on these findings, there is the need for all the major stakeholders of vocational education within and outside Nigeria to collaborate in order to promote good governance practices in the utilization of funds for execution of projects by vocational education administrators.